2016
DOI: 10.1186/s12575-016-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Protocol for Packaging Pseudotyped Integrase Defective Lentivirus

Abstract: BackgroundA number of integrase defective lentiviral (IDLV) packaging systems have been developed to produce integration deficient lentiviruses for gene delivery and epichromosomal expression. However, despite their growing demand, a comparative study to systemically evaluate the performance efficiency of different mutants on virus packaging and gene expression has not been done.ResultsSite-directed mutagenesis was used to generate five integrasedeficient mutants for non-integrative lentiviral packaging (NILVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Pseudotyping is often used in the production of recombinant viruses and involves packaging the genetic components of the virus (DNA or RNA) with envelope proteins derived from a different virus. [28][29][30] This method allows one to select viral envelope proteins to alter host tropism, which may result in enhanced infection of the recombinant virus. 31,32 The G glycoprotein of the vesicular stomatitis virus glycoprotein (VSVG) is frequently used for viral pseudotyping, owing to its broad tropism and high efficacy in transduction, and in fact most of the retroviruses approved for clinical trials are pseudotyped with VSVG.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudotyping is often used in the production of recombinant viruses and involves packaging the genetic components of the virus (DNA or RNA) with envelope proteins derived from a different virus. [28][29][30] This method allows one to select viral envelope proteins to alter host tropism, which may result in enhanced infection of the recombinant virus. 31,32 The G glycoprotein of the vesicular stomatitis virus glycoprotein (VSVG) is frequently used for viral pseudotyping, owing to its broad tropism and high efficacy in transduction, and in fact most of the retroviruses approved for clinical trials are pseudotyped with VSVG.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we and others demonstrated that the vesicular stomach virus envelope glycoprotein (VSVG)-pseudotyped lentiviruses have a super high infection rate of ~100% [ 36 , 37 ]. In this study we chose VSVG-pseudotyping protocol for lenti-Cre virus production, and examined whether VSVG-pseudotyped lenti-Cre-GFP could deliver, express and subsequently edit the knockin floxed-RFP-Puro in reporter cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we had developed a system for delivering various genes into cells using either lentiviral or AAV particles [ 36 , 38 ]. We initially selected the lentiviral system because of its favorable features: (1) Lentiviral transduction is an efficient way to create a stable cell line expressing Cre in almost any mammalian cell type including stem cells and non-dividing cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images of living cells were typically taken using fluorescence microscopy as reported [33]. To show the intensity of GFP expression, both fluorescent and phase contrast images were recorded.…”
Section: Live Fluorescence Microscopymentioning
confidence: 99%